2021
DOI: 10.1093/milmed/usaa446
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Assay of Hind Limb in Multiple Animal Models

Abstract: Introduction Measuring hemodynamic characteristics of injured limbs is paramount to early identification of potentially damaging ischemic conditions, but can often prove difficult attributable to a multitude of factors. Here, we present an in vivo optical imaging technique to characterize pulsatile blood flow quality through the distal extremity in multiple animal models that replicate the signs of distal extremity ischemia. The purpose of this study is to examine the feasibility of the optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Despite differences in the anatomy and/or physiology of different animals used in the study, multiple authors in this review have demonstrated similar findings using the same methodology in both rat and large animal models. [ 5 , 29 , 41 ] We could not find definitive evidence that anatomic differences associated with small animal models adversely affected compartment syndrome research outcomes. While large animals may provide better anatomic similarity relative to humans, they are associated with significant additional research cost and it is our opinion that authors must weigh the benefits of anatomic similarity with their over-arching research goals when selecting a species.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Despite differences in the anatomy and/or physiology of different animals used in the study, multiple authors in this review have demonstrated similar findings using the same methodology in both rat and large animal models. [ 5 , 29 , 41 ] We could not find definitive evidence that anatomic differences associated with small animal models adversely affected compartment syndrome research outcomes. While large animals may provide better anatomic similarity relative to humans, they are associated with significant additional research cost and it is our opinion that authors must weigh the benefits of anatomic similarity with their over-arching research goals when selecting a species.…”
Section: Discussionmentioning
confidence: 87%
“…Forty-one studies were included in the final review (Tables 1-4). [1–41] A total of 865 animals were included with an average of 22.2 animals per study. Dogs (31.7%) were the most used model species, followed by pigs (26.8%) and rats (24.4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations